2014
DOI: 10.2478/arsm-2014-0003
|View full text |Cite
|
Sign up to set email alerts
|

The cardiometabolic benefits of flavonoids and dark chocolate intake in patients at risk

Abstract: Scientific research proves that the cardiac and the metabolic functions are improved by the consumption of flavonoids, natural elements found in cocoa. The dark chocolate is the main alimentary compound rich in flavonoids, and for this reason it can be used to prevent some cardiometabolic disorders. This study aims to demonstrate the relationship between chocolate consumption and the cardiometabolic disorders risk in 85 patients hospitalized in Internal Medicine Unit of Emergency Hospital "St. Apostle Andrew" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Among obese mice feeding a high-fat diet supplemented with high polyphenolic cocoa it was reported a decrease on body weight gain, insulin resistance, inflammation, and liver steatosis with concomitant increase on fecal lipid excretion [ 30 ]. In this regard, daily intake of chocolate had been associated with decreased risk of overall cardiovascular disease (19%), coronary artery disease (23%), incident type 2 diabetes mellitus (28%), and cerebrovascular disease (32%) in humans [ 31 ]. The present study with a small sample confirmed the data from previous studies with larger populations [ 8 , 9 , 10 , 11 , 12 , 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among obese mice feeding a high-fat diet supplemented with high polyphenolic cocoa it was reported a decrease on body weight gain, insulin resistance, inflammation, and liver steatosis with concomitant increase on fecal lipid excretion [ 30 ]. In this regard, daily intake of chocolate had been associated with decreased risk of overall cardiovascular disease (19%), coronary artery disease (23%), incident type 2 diabetes mellitus (28%), and cerebrovascular disease (32%) in humans [ 31 ]. The present study with a small sample confirmed the data from previous studies with larger populations [ 8 , 9 , 10 , 11 , 12 , 19 , 29 ].…”
Section: Discussionmentioning
confidence: 99%